Accuracy of Pedicle Screw Placement with Robotic Guidance System: A Cadaveric Study. Issue 24 (December 2015) - Fujishiro, Takashi; Nakaya, Yoshiharu; Fukumoto, Shingo; Adachi, Shu; Nakano, Atsushi; Fujiwara, Kenta; Baba, Ichiro; Neo, Masashi
Abstract : Study Design: A cadaveric study. Objective: To investigate the accuracy of pedicle screw placement using a robotic guidance system (RGS). Summary of Background Data: RGS is a unique surgery assistance-apparatus. Although several clinical studies have demonstrated that RGS provides accurate pedicle screw placement, very few studies have validated its accuracy. Methods: A total of 216 trajectories performed with the assistance of the RGS in eight cadavers were evaluated. The RGS was used, with different mounting platforms, to drill pilot holes in the thoracic and lumbosacral spine, using 3-mm diameter fiducial wires as trajectory markers. Deviation between the preoperative plan and executed trajectories was measured at the entry points to the vertebrae and at a depth of 30 mm along the wire. Both the deviation from the preoperative plan and the wire position were evaluated in the axial and sagittal planes using computed tomography (CT). Results: The average deviation from the planned wire placement was 0.64 ± 0.59 mm at the entry point and 0.63 ± 0.57 mm at a depth of 30 mm in the axial plane, and 0.77 ± 0.62 mm and 0.80 ± 0.66 mm, respectively, in the sagittal plane. The magnitude of deviation was not affected by the vertebral level or the platform used. The use of an open approach achieved greater screw placement accuracy at a depth of 30 mm in the sagittal plane, compared with the percutaneous approach. The fiducials were placed completely within the pedicle in 93.9% of trajectories in the axial plane (n = 164 pedicles with a width ≥5 mm) and 98.6% in the sagittal plane (n = 216). Conclusion: In this cadaveric study, RGS supported execution of accurate trajectories that were equal or slightly superior to reports of CT-based navigation systems. Level of Evidence: N/A